Omega-3 fatty acids supplementation protects the retina from age-associated degeneration in aged C57BL/6J mice. Issue 1 (10th November 2019) - Prokopiou, Ekatherine; Kolovos, Panagiotis; Georgiou, Christos; Kalogerou, Maria; Potamiti, Louiza; Sokratous, Kleitos; Kyriacou, Kyriacos; Georgiou, Tassos
Abstract : Objective: To evaluate the therapeutic effects of omega-3 (ω3) fatty acids in the retina of aged mice when the blood arachidonic acid (AA)/eicosapentaenoic acid (EPA) ratio is maintained between 1.0 and 1.5. Methods and analysis: Aged (24-month-old) wild-type C57BL/6J mice were allocated to two groups: ω3 treated and untreated. Treatment with ω3 was by daily gavage administration of EPA and docosahexaenoic acid for 60 days. Gas chromatography was used to identify and quantify fatty acids in the blood and retina. To count lipofuscin granules and measure the photoreceptor layer, eyecups were examined histologically using transmission electron microscopy and light microscopy. We also analysed eyecups using mass spectrometry-based proteomics. Results: AA levels were lower, and EPA levels were higher, in the blood and retinas of the ω3-treated group than in the untreated group, resulting in a lower AA/EPA ratio. The ω3-treated group also showed significantly fewer lipofuscin granules and a thicker outer nuclear layer than the untreated group. Proteomic analysis revealed significantly greater expression of myelin basic protein, myelin regulatory factor-like protein, myelin proteolipid protein and glial fibrillar acidic protein in the ω3-treated group than in the untreated group. Three different pathways were significantly affected by ω3 treatment: fatty acid elongation, biosynthesis of unsaturated fatty acids and metabolic pathways. Conclusion: Two months of ω3 supplementation (when the blood AA/EPA 1.0–1.5) in aged mice reduced lipofuscin granule formation in the retina and protected the photoreceptor layer, suggesting that ω3 supplementation slows normal age-related retinal degeneration.